Severe but Self-Limiting Polyarthralgia with Functional Impairment Following ChAdOx1 nCov-19 Vaccination in an Elderly Recipient - Joel Ern Zher Chan (MDPI AG, 2021)
A 79-year-old female patient with no pre-existing rheumatological conditions presented with severe functional impairment secondary to polyarthralgia, most likely an adverse reaction following her first dose of Oxford/AstraZeneca ChAdOx1 nCov-19 vaccination against SARS-CoV-2, the causative agent of Coronavirus Disease 2019 (COVID-19). The presentation mimicked clinical features of polymyalgia rheumatica and was distinctive in its pattern and delayed onset. Its severity in an elderly patient was significant against trial findings of decreasing reactogenicity of ChAdOx1 nCov-19 vaccine with increasing age, and traumatic to the patient. Acute phase reactants were elevated, consistent with recent similar reports among mostly elderly, female patients. New onset rheumatological conditions and flares of pre-existing, well-controlled conditions had been well established in COVID-19 and, to a lesser extent, post-vaccination. Viral arthralgias as a distinct clinical entity in COVID-19 is only beginning to be recognized. It could be that this case report represents a similar entity which occurs following vaccination against SARS-CoV-2. Despite this, the benefits of vaccination continue to outweigh such risks, although this case report is important for providing understanding of clinical progression when such reactions occur, aiding in patient discussions and clinical decisions to weigh up further investigations or empirical treatment against reassurance and close monitoring.